Data on the move: How household energy data travel and empower - Jhagroe, Shivant (STS Encounters, 2020)
Even though Science and Technology Studies has highlighted how things and publics participate in energy assemblages, the specific role of big data has received relatively little attention. This paper examines the politics of energy data in relation to residential grid management. Informed by the concept ‘data journey’, developed by Bates et al. (2016), it proposes an ‘energy data journey’ approach and focusses on two questions: how are big data of smart homes produced and how do they travel? And who is empowered by this energy data production and movement? The paper addresses these questions in the empirical context of a Dutch-Belgian pilot project that has designed and tested energy management of a smart home. The empirical analysis shows how energy data and household profiles are created and travel through different cyber-physical locations to serve different purposes. The use of specific ‘home energy profiles’ is crucial and contributes to neoliberal energy management as it focusses on self-monitoring tools and users’ responsibility, while empowering commercial tech-companies and high income groups. The final section reflects on the cyber-materiality of energy data and the techno-politics of energy data more broadly. The paper argues that an energy data journey approach is productive for STS researchers when critically reflecting on the agency and politics of energy data.